2022
DOI: 10.5510/ogp2022si200768
|View full text |Cite
|
Sign up to set email alerts
|

Changing climatic indicators and mapping of soil temperature using Landsat data in the Yangan-Tau UNESCO global geopark

Abstract: Changes in key climate index affect ecosystems and biodiversity. In this regard, the assessment of the climatic conditions is of particular relevance. This study presents the results of an analysis of climate change and digital mapping of soil temperature in the Yangan-Tau UNESCO Global Geopark (Russia). The steady increase in air temperature was revealed, which causes an increase in the sum of active temperatures and the duration of the warm period of the year. Annual total precipitation during 1966-2020 chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Increasing average annual temperatures and decreasing precipitation have a leading influence on salinization processes in arid and semi-arid regions [59]. Previously, numerous studies have demonstrated changes in climatic indicators in the Ural region [42,[60][61][62], which contribute to soil salinity. As previously mentioned, the key factor driving soil salinization in the research region is groundwater level/table.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing average annual temperatures and decreasing precipitation have a leading influence on salinization processes in arid and semi-arid regions [59]. Previously, numerous studies have demonstrated changes in climatic indicators in the Ural region [42,[60][61][62], which contribute to soil salinity. As previously mentioned, the key factor driving soil salinization in the research region is groundwater level/table.…”
Section: Discussionmentioning
confidence: 99%
“…Natural disturbances such as storms, fires, and disease outbreaks are relatively common in the region and in the reserve, which also affect tree growth and mortality [18][19][20]. The above-mentioned negative factors are also exacerbated by climate change, which has been established in the study region [21][22][23]. Changes in temperature, precipitation patterns, and other climatic factors can impact the availability of resources and create new challenges for forest managers [24].…”
Section: Forests Of the Reservementioning
confidence: 99%
“…The park is a popular place for recreation and the largest number of visitors to the park arrive during the hot season. As a result, the negative climatic impact in the region is exacerbated by the increased level of recreational load [14][15][16]. The study area is located in the west part of the republic, within the Kandrykul-Usen and Usensko-Ryasky physical-geographical districts of the Belebey upland-level typical forest-steppe district [17].…”
Section: Study Areamentioning
confidence: 99%